2019
DOI: 10.1186/s41938-019-0109-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of plant extracts as inducers to challenge leaf rust of wheat

Abstract: Five plant extracts, i.e., henna, Lawsonia inermis; acalypha, Acalypha wilkesiana; chinaberry, Melia azedarach; pomegranate, Punica granatum; and lantana, Lantana camara, were tested as inducers to protect wheat against leaf rust infection caused by Puccinia triticina Eriks. The plant extracts were applied pre-infection on susceptible wheat cultivar "Gemmiza-7" under field conditions during two growing seasons (2016/2017 and 2017/2018). All the tested plant extracts were found to be effective against the leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
(27 reference statements)
3
20
0
4
Order By: Relevance
“…The obtained promotion effect on growth criteria is in agreement with the data recorded from studying the impacts of aqueous extracts of four medicinal plants ( Eclipta prostrate, Wood fordia fructicosa, Ageratum conyzoides and Cannabis sativa ) on the seed germination, seedling growth and biomass production of Triticum aestivum (wheat) and Pisum sativum (pea) [ 40 ]. Additionally, the obtained results are in line with Draz et al [ 41 ] who demonstrated that the extracts from lantana, Lantana camara ; henna, Lawsonia inermis ; pomegranate, Punica granatum ; acalypha, Acalypha wilkesiana and chinaberry, Melia azedarach significantly increased wheat yield components in terms of 1000-kernel and spike weight compared to the non-treated control. Moreover, Shabana et al [ 42 ] and Nagwa and Iman [ 43 ] found that the foliar spraying of plant extracts (Brazilian pepper, pomegranate, neem, garlic, cactus, and eucalyptus) significantly increased wheat yield components, including spike weight and 1000-kernel weight.…”
Section: Resultssupporting
confidence: 89%
“…The obtained promotion effect on growth criteria is in agreement with the data recorded from studying the impacts of aqueous extracts of four medicinal plants ( Eclipta prostrate, Wood fordia fructicosa, Ageratum conyzoides and Cannabis sativa ) on the seed germination, seedling growth and biomass production of Triticum aestivum (wheat) and Pisum sativum (pea) [ 40 ]. Additionally, the obtained results are in line with Draz et al [ 41 ] who demonstrated that the extracts from lantana, Lantana camara ; henna, Lawsonia inermis ; pomegranate, Punica granatum ; acalypha, Acalypha wilkesiana and chinaberry, Melia azedarach significantly increased wheat yield components in terms of 1000-kernel and spike weight compared to the non-treated control. Moreover, Shabana et al [ 42 ] and Nagwa and Iman [ 43 ] found that the foliar spraying of plant extracts (Brazilian pepper, pomegranate, neem, garlic, cactus, and eucalyptus) significantly increased wheat yield components, including spike weight and 1000-kernel weight.…”
Section: Resultssupporting
confidence: 89%
“…In contrast, Draz et al (2019), testing inducers of resistance in wheat culture against Puccinia triticina infection, under field conditions, with artificial inoculation of the pathogen, observed increases in the WTG (g) yield component and also in the HW, when using the extract of lantana (Lantana camara) and diniconazole fungicide, being 31 and 27%, respectively for WTG and 13 and 11%, respectively, for HW.…”
Section: Resultsmentioning
confidence: 94%
“…Since the 2 million hectares cultivated and the production of 5.4 million tons do not supply the country consumption, wheat (Triticum aestivum L.) has great economic importance for Brazil due to strong demand for its derivatives (Conab 2018). The diseases that occur in the crop during the whole cycle, and when under favorable conditions, can make the cultivation unfeasible (Draz et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pollution problems in the environment and the toxic effects of synthetic chemicals on non-target organisms have prompted investigations on exploiting pesticides of plant origin. Natural plant products and their analogues resulted in being an important source of new agricultural chemicals [ 217 , 218 ] used in control of insect pests [ 219 ], plant diseases [ 9 , 10 , 220 , 221 , 222 , 223 , 224 ], and as a bird repellent [ 225 , 226 , 227 ]. Several studies have shown the importance of natural chemicals as a possible source of non-phytotoxic, systemic, and easily biodegradable alternative pesticides [ 228 , 229 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Similarly, lupine seeds were successfully treated with extracts of Nerium oleander , Eugenia jambolana, and Citrullus colocynthis [ 8 ]. Clove, garden quinine, Brazilian pepper, anthi mandhaari, black cumin, white cedar, neem, and rice extracts were used in the control of leaf rust in wheat [ 9 , 10 ]. It is unclear if these products can improve plant vigor and response to other fungal pathogens, especially under organic farming conditions, in which plants are more susceptible to the pathogen-induced damage.…”
Section: Introductionmentioning
confidence: 99%